Imprecisiones de índole nutricional en el contenido de informaciones relativas a la nutrición publicadas en los diarios de mayor lectoría de Lima Metropolitana - Friedman Oxenstein, Jackelyn (2013)
Introduction: The media publishing health issues have become an intermediary between health organizations and concerned citizens about their health and well-being.(1) The way in how they communicate scientific nutritional issues can have important effects in population’s attitudes and behaviors, and therefore in their welfare.(2) While the attention to health and nutrition issues disseminated by the media is growing, people feel badly informed.(3) Objective: To determine the presence of nutritional inaccuracies in the content of nutrition related information published in the eight newspapers with the largest readership of Lima Metropolitana. Material and methods: The type of study was non-experimental, descriptive, cross - sectional. The research method was qualitative. From September 17th, 2012 to october 17th, 2012, 31 copies of each of the selected newspapers were collected: Trome, Ojo, El Comercio, Peru 21, Depor, Correo, El Popular and Ajá. (The total amount of newspapers was 248). Results: 144 nutrition related informations were found, of which 109 had nutritional inaccuracies in their content, equivalent to 75,7%. 87 of them were present in popular newspapers (Trome, Ojo, El Popular and Ajá), while the remaining 22 were part of the serious2 newspapers (El Comercio, Perú 21 and Correo). Sports newspaper (Depor) did not provide nutrition related information during the study time. Six kinds of nutritional inaccuracies that appeared most frequently in the content of information were detected. These were: (1) Not specifying the recommended amount of food, (2) Not specifying the appropriate form of consumption of food, (3) Not specifying the sources from which the information was obtained, (4) Lack of relevant information, (5) Presence of confusing information and (6) Presence of wrong information. Conclusions: The analysis of the content of the nutrition related information found in the eight newspapers with the largest readership in Lima Metropolitana, prove that most of these informations (75,7%) present nutritional inaccuracies. Therefore, it is clear that the journalistic criteria of validation, prudence and rigor are not met when preparing these reports. The results also reflect the urgency and importance of the work between nutritionists and journalists responsible for disseminating news related to the field of nutrition and healthy eating, which will allow the population to receive adequate information and be able to change attitudes and behaviors to improve their health, considering the impact caused by the media in the eating habits of its users.